Evaluation and modification of spike - tooth and rasp - bar type paddy threshers - SAILAJA L; Dr. M Sivaswami (Guide) (Tavanur 1993 Kelappaji College of Agricultural Engineering and Technology)
Evaluation and modification of spike - tooth and rasp - bar type paddy threshers
Evaluation and modification of spike - tooth and rasp - bar type paddy threshers